Jim Stoppani's encyclopedia of muscle & strength - Stoppani, James 1968- (Human Kinetics, 2014)
A research-based book that covers all facets of optimising the development of muscle and strength. Containing 382 exercises covering for 13 muscle groups and the whole body, it shows the proper technique for each exercise, tailored to the type of resistance used, be it free weights, weight machines or body weight.